AB0115 SECUKINUMAB THERAPY DOES NOT AFFECT NEUTROPHIL HOST DEFENCE IN PSORIATIC ARTHRITIS. (2nd June 2020) - Cross, A.; Hawkes, J.; Frankland, H.; Mediana, A.; Wright, H.; Goodson, N.; Edwards, S.; Moots, R.
Abstract : Background: Biologic therapies have revolutionised therapy in inflammatory diseases such as psoriatic arthritis (PsA), driving major improvements in outcomes. Th17 cells appear to play a key role in the pathogenesis of PsA, and IL-17 can trigger the release of chemoattractants such as CXCL8 and CCL20, leading to the further infiltration of other immune cells including neutrophils. Infiltrating activated neutrophils can themselves generate a range of chemoattractants which may amplify and sustain the inflammatory response. Therapeutic targeting of IL-17 with biologics such as secukinumab offers great benefit in PsA by blocking this inflammatory cycle: however the interaction of this agent with neutrophils, key components of host defence as well as potential mediators of this disease, is not known. Objectives: This study aimed to measure key aspects of neutrophil function to determine: a) changes in the functions of circulating neutrophils in PsA patients pre-therapy, compared to age- and sex-matched healthy controls and b) if these functions changed in PsA patients 12-weeks post-secukinumab therapy. Methods: Neutrophils were isolated from venous blood of 16 PsA patients and 10 healthy controls. Key neutrophil functions were measured at baseline and 12 weeks: reactive oxygen species (ROS) production, apoptosis (+/- TNF and GM-CSF), phagocytosis, receptor expression and chemotaxis. Changes in gene expression pre- and 12-weeks post-therapy (n=5 PsA) were measured using RNAseq. Results: PsARC response was observed in 70.6% of participants on secukinumab therapy at 12 weeks. There were no significant differences in ROS production, phagocytosis or chemotaxis in PsA patients at baseline (compared to healthy controls) or during therapy. Chemotaxis towards IL-8 in PsA patients at baseline was decreased compared to that of healthy controls, but this difference did not reach statistical significance. Surface levels of activation markers CD11b/CD18 and CD63 were increased in PsA patients at 12-weeks compared to baseline, while surface levels of CD16 decreased. RNA-seq analysis indicated down-regulation of pathways mediated by IL-17A, oncostatin M, TWEAK (TNFSF12) and CCL2 during therapy, but up-regulated expression of pathways involving de novo protein biosynthesis. Conclusion: Therapy with secukimumab in PsA did not significantly affect neutrophil host defence functions. The changes that were seen in circulating neutrophils indicate selective up- and down-regulation of functions that may reflect potential alterations in local or systemic cytokines, and/or an increase in the circulating pool of activated neutrophils that are no longer recruited into sites of inflammation because of the down-regulation of the local IL-17/CXCL8 signalling network. Disclosure of Interests: Andrew Cross: None declared, Jennifer Hawkes: None declared, Helen Frankland: None declared, Ayren Mediana: None declared, Helen Wright Grant/research support from: Novartis supporting this study, Nicola Goodson Grant/research support from: Novartis supporting this research, Steven Edwards Grant/research support from: Novartis supporting this work, Robert Moots Grant/research support from: Novartis supporting this work, Consultant of: a variety of companies including Novartis, Speakers bureau: a variety of companies including Novartis